Epidemiological profile of patients undergoing surgical treatment of ankle fractures in a tertiary hospital - Piccini, Cleiton Francisco; Endres, Gaston; do Prado, João Marcus; Scherer, Mateus Breitenbach (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the epidemiological profile of ankle fractures treated surgically in a tertiary hospital. Methods: A retrospective epidemiological study was performed. The medical records of patients with ankle fractures who underwent surgery between January and December 2017 were reviewed. The parameters assessed included age, gender, injured side, exposure (open vs closed), Arbeitsgemeinschaft für steosynthesefragen (AO) fracture classification, trauma mechanism, time to definitive treatment, and early postoperative complications. Results: The male gender was predominant (64.6%). Twenty-two fractures (50%) resulted from traffic accidents, 16 (36.4%) of which involved a motorcycle. The mean age of these patients was 28.25 years. The AO 44-B ankle fracture was the most common injury (70.4%). Eight (18.2%) were open fractures. The mean time to definitive treatment was 5.9 days. Early postoperative complications occurred in two patients (4.5%). Conclusion: Ankle fractures treated in a tertiary hospital affect young victims of high-energy accidents, mainly involving motorcycles. Level of Evidence IV; Therapeutic Studies; Case Series.